One‐Step Formation of Hybrid Nanocrystal Gels: Deposition of Metal Domains on CdSe/CdS Nanorod and Nanoplatelet Networks (Advanced Optical Materials 17/2021). Issue 17 (4th September 2021) - Zámbó, Dániel; Schlosser, Anja; Graf, Rebecca T.; Rusch, Pascal; Kißling, Patrick A.; Feldhoff, Armin; Bigall, Nadja C.
Abstract : In article number 2100291, Nadja C. Bigall and co‐workers report a one‐step synthesis route to prepare different hybrid semiconductor–metal nanocrystal gel networks. The novel approach includes the simultaneous formation of the hyperbranched semiconductor dot‐in‐rod and nanoplatelet backbones as well as their decoration with noble metals and transition metal‐based domains without using light, heat, or any external chemical trigger. The conduction band/Fermi level offset facilitates an efficient charge carrier separation upon illumination in the hybrid gel structures.